O catolicismo popular brasileiro: notas em torno da sua invenção historiográfica - Ferreira de Sousa, Emerson José (Temporalidades, 2022)
This proposal consists in demonstrating that popular Catholicism in Brazil has been constituted as an invention of the vast historical, sociological and anthropological literature that discuss Catholic phenomena, seeking to define them conceptually. In the theoretical field, we are mainly inspired by the conceptions of Roger Chartier and Michel de Certeau, for elucidating that the concept of popular culture has been defined especially from the intellectual positions and actions that constitute the disciplinary arenas dedicated to it. As a methodology, we conducted a bibliographic discussion using the main works and authors from the field of history, sociology and anthropology that deal with Catholic religiosity in Brazil. The text shows that the analysis of the social realities of Brazil and the cultural hybridism that characterize them were decisive to classify themselves as popular to Catholic religiosity that transcends institutional spaces.